The Precision of Qibla Direction in Masjid Jami' At Beber District: A Comprehensive Study From the Perspectives of Astronomy and Local Scholars - Kusdiyana; Akhmad Nadirin; Rifki Al Wafi (NUSANTARA: Journal Of Law Studies, 2023)
Mosques play a central role as places of worship for Muslims, yet observations indicate that the qibla accuracy in several mosques in Beber District has not been reassessed since their construction. For instance, Masjid Al-Ma’mur in Ciawigajah Village deviates by 9° 31' from the expected qibla direction. This research aims to assess the qibla accuracy in mosques of Beber District and explore the responses from scholars and the perspective of celestial science regarding this inaccuracy. The research methodology is qualitative with a field research approach. The Mizwala Qibla Finder (MQF) is utilized as a tool for measuring qibla accuracy. Primary data is obtained through observations, interviews, documentation, and secondary data from relevant literature. Data analysis is conducted using a descriptive-verification approach. Among the ten mosques studied, three exhibit deviations in qibla direction. Scholars like KH. Ahmad highlight the seriousness of this issue as it can impact the direction of prayer. However, other scholars, such as KH. Muhtadi, suggest that technical aspects like qibla direction should not be overly emphasized. Scholars' responses and the celestial science perspective provide diverse insights into the significance and handling of qibla accuracy issues within the context of diverse worship practices in mosques of Beber District